Research Institutes/Center scientific production at the Faculty of Medicine of Universidad Nacional Mayor de San Marcos - Pacheco-Romero, José (2012)
Objectives: To determine research production at the Faculty of Medicine, UNMSM. Design: Retrospective, observational, transversal type study. Setting: Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Seven research institutes and one investigation center investigators. Interventions: Study of investigator cards elaborated by the Faculty of Medicine Research Unit and filled by members of the Andean Biology, Experimental Surgery, Ethics in Health, Clinical Investigations, Tropical Medicine, and Pathology Research Institutes as well as by Biochemistry and Nutrition Investigation Centre members. Data analysis used Epi- Info system version 3.5.1 and Anova statistical model for analysis of variance. Main outcome measures: Scientific investigations and publications. Results: From the 116 members of the six Research Institutes/Centre only 54 from five Institutes and the Centre filled the investigator card and reported they had done 659 investigations during the six-year period and published an average of two investigations per investigator-year; 19% never published during the period studied. There was no significant difference of investigators gender, academic degree, teaching hours, profession or Institute/Centre, but members of one Institute seemed to investigate more. Conclusions: Docents-researchers filling the card reported 659 investigations between 2004-2009 averaging two investigations per researcher-year. One of the Institutes seemed to have done more research. Nineteen per cent of the investigators did not publish during those years and those publishing did it seven times more in national than international journals.